Sensitivity and influence of the internal and external medium on the textile and wood materials in the museum - Fatimi, aicha (The Algerian Historical Journal, 2026)
The sources of organic materials vary and vary, some of which are from an animal or plant source and are obtained directly, such as: wood, bone, and ivory, or indirectly through their manufacture such as textiles, manuscripts, and leather, and the latter are usually very sensitive to various environmental conditions, such as: Light, heat, high humidity, pollution and other factors of the preservation medium, and in this study we will highlight the most important internal and external factors that have a negative impact on the textile material inside the museum, as the latter is among the organic materials that are most sensitive to external factors, and the aim is to identify The most important factors that lead to damage and how it can affect the material.